If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 = -6tx + -8 Reorder the terms: 46 = -8 + -6tx Solving 46 = -8 + -6tx Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6tx' to each side of the equation. 46 + 6tx = -8 + -6tx + 6tx Combine like terms: -6tx + 6tx = 0 46 + 6tx = -8 + 0 46 + 6tx = -8 Add '-46' to each side of the equation. 46 + -46 + 6tx = -8 + -46 Combine like terms: 46 + -46 = 0 0 + 6tx = -8 + -46 6tx = -8 + -46 Combine like terms: -8 + -46 = -54 6tx = -54 Divide each side by '6x'. t = -9x-1 Simplifying t = -9x-1
| b/3+1/8=19.24 | | 3(2x-5)+x=4(x+7)-4 | | g=5*3.14*k | | 3z+8/25+1/5=z | | e^4y=4 | | 1/2+2c=3/5 | | 7m-5n= | | 5x+3=-30+2x | | 7(z-2)=-6z-8+13z | | 50h=190-45h | | b/4+1/7=19 | | 1/4y=-5x+7 | | 3(u-1)-1=-3(-4u+6)-u | | 1/4(3x-1)=2(x-2) | | x/9x=2/3 | | 29/5=k-1/5(-10k-4) | | 4/3x=44 | | 2(x-3)=5(2x+6) | | -6(9x-8)=425 | | (16+a)+11= | | 18+2x=9x+4 | | 2(x+5)=6x+10-4x | | 5(t+3)+9=3t+(-6)+6 | | 3/2(y+2)=g | | 2/3(3x-6)=10 | | 6[3-(4+4x)]=-8+2(1-14x) | | 21x+7=3x+16 | | 4-5x=-26 | | 4/p=16/5 | | 9(m+1)-6m=3m+6 | | 2-5/16 | | 2x8-2+6/3=0 |